The (un)expected consequences of the teacher's (emotional) labor. Inspirations from politically and critically oriented affect theories - Renata Góralska (Studia z Teorii Wychowania)
The aim of the article is to describe the teacher’s (emotional) labor and its relationships with the formation of the teacher’s subjectivity. This relationship is especially visible when the relations between the teacher’s emotions and professional work are shown from the perspective of theoretical analyses and research in the field of the affective turn, especially the so-called "affective economies". Based on selected critical and political theories of emotions (i.a. Brian Massumi, Sarah Ahmed, and Teresa Brennan), the teacher’s (emotional) labor is presented here as a tool of auto-(trans)formations and (auto-)reflection and, at the same time, as a place of the affective marginalization of the teacher’s subjectivity and impoverishment of his or her agency. The presented way of conceptualizing emotional labor is a new look at the teacher’s emotions. It provides educational theorists and pedeutologists with analytical tools for empirical research and is also a voice in the discussion, an argument for considering affect in teacher education.